Cost-effectiveness of testing for latent tuberculosis infection in people with HIV. (1st January 2022) - Auguste, Peter E.; Mistry, Hema; McCarthy, Noel D.; Sutcliffe, Paul A.; Clarke, Aileen E.
Abstract : Objective: The aim of this study was to estimate the cost-effectiveness of screening strategies for predicting LTBI that progresses to active tuberculosis (TB) in people with HIV. Design: We developed a decision-analytical model that constituted a decision tree covering diagnosis of LTBI and a Markov model covering progression to active TB. The model represents the lifetime experience following testing for LTBI, and discounting costs, and benefits at 3.5% per annum in line with UK standards. We undertook probabilistic and one-way sensitivity analyses. Setting: UK National Health Service and Personal Social Service perspective in a primary care setting. Participants: Hypothetical cohort of adults recently diagnosed with HIV. Interventions: Interferon-gamma release assays and tuberculin skin test. Main outcome measure: Cost per quality-adjusted life year (QALY). Results: All strategies except T-SPOT.TB were cost-effective at identifying LTBI, with the QFT-GIT-negative followed by TST5mm strategy being the most costly and effective. Results indicated that there was little preference between strategies at a willingness-to-pay threshold of £20 000. At thresholds above £40 000 per QALY, there was a clear preference for the QFT-GIT-negative followed by TST5mm, with a probability of 0.41 of being cost-effective. Results showed that specificity for QFT-GIT and TST5mm were the main drivers of the economic model. Conclusion: Screening for LTBI has important public health and clinical benefits. Most of the strategies are cost-effective. These results should be interpreted with caution because of the paucity of studies included in the meta-analysis of test accuracy studies. Additional high-quality primary studies are needed to have a definitive answer about, which strategy is the most effective. Abstract : Supplemental Digital Content is available in the text